THE ANALYSIS OF THE FINANCIAL STATEMENTS IN SUPPORTING THE LENDING DECISION AT PT. BANK PERKREDITAN RAKYAT NUSA UTARA - Nur, Eva Debby; Elim, Inggriani (Universitas Sam Ratulangi, 2015)
The Bank as the financial institution lending business activity must hold a selection process to filter out any loans that come in, so the loans do not become bad loans that could harm the bank. The purpose of this study is an analysis of bank financial statements and reports profit / loss ratio analysis, so the bank can determine and evaluate the financial statements of borrowers to take lending decisions. The analytical method used is descriptive analysis by comparing the performance of companies in the form of the financial statements of banks for 3 years and ratio analysis as one of the basic components for determining the credit decision. It can be concluded that in the liquidity of the years 2012-2014, the Current Ratio and Quick Ratio increased, while Cash and Inventory Ratio to Net Working Capital (NWC) has decreased. Solvency level of the 2012-2014 Debt to Assets Ratio and Debt to Equity Ratio decreased, while Primary rose. The level of profitability from the years 2012-2014 Return on Investmen (ROI) increased, while the Return on Equity (ROE) of 2012-2013 has decreased years 2013-2014 has increased. The results showes BPR no longer able to provide credit, unless there is additional capital from the owners of the bank. Keyword: liquidity ratio, solvability ratio, profitability ratio